2016
DOI: 10.1111/jnc.13545
|View full text |Cite
|
Sign up to set email alerts
|

Oxaloacetate enhances neuronal cell bioenergetic fluxes and infrastructure

Abstract: We tested how the addition of oxaloacetate (OAA) to SH-SY5Y cells affected bioenergetic fluxes and infrastructure, and compared the effects of OAA to malate, pyruvate, and glucose deprivation. OAA displayed pro-glycolysis and pro-respiration effects. OAA pro-glycolysis effects were not a consequence of decarboxylation to pyruvate because unlike OAA, pyruvate lowered the glycolysis flux. Malate did not alter glycolysis flux and reduced mitochondrial respiration. Glucose deprivation essentially eliminated glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 17 publications
1
42
0
2
Order By: Relevance
“…OAA has been described as a potent neuroprotectant because of its role as a glutamate scavenger, which is an important mediator of neuronal degeneration . In a cell line derived from a human neuroblastoma, OAA was found to increase the glycolytic flux and NAD/NADH ratio . OAA is also known to attenuate zinc‐induced cell death in both retinal pigmented epithelium and insulinoma cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OAA has been described as a potent neuroprotectant because of its role as a glutamate scavenger, which is an important mediator of neuronal degeneration . In a cell line derived from a human neuroblastoma, OAA was found to increase the glycolytic flux and NAD/NADH ratio . OAA is also known to attenuate zinc‐induced cell death in both retinal pigmented epithelium and insulinoma cells .…”
Section: Discussionmentioning
confidence: 99%
“…(42) In a cell line derived from a human neuroblastoma, OAA was found to increase the glycolytic flux and NAD/NADH ratio. (43) OAA is also known to attenuate zinc-induced cell death in both retinal pigmented epithelium and insulinoma cells. (44) Although specific pathways have not yet been clearly defined, OAA is potentially associated with increased cell viability and mitochondria preservation, but also antioxidative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, OAA treatment achieved broader beneficial effects in the brain, including insulin pathway activation, neurogenesis, and reduced neuroinflammatory markers (Wilkins et al, ). When tested on SH‐SY5Y neuroblastoma cells, OAA enhanced glycolysis and cell respiration, and this correlated with an increased NAD+/NADH ratio (Wilkins et al, ). As mentioned above, OAA is being tested in a Phase 1b clinical trial in AD subjects (NCT02593318; Table ).…”
Section: Treatment Strategies Targeting Mitochondria: Novel Approachementioning
confidence: 99%
“…OAA can also be converted to phosphoenolpyruvate (PEP) within the cytoplasm as a part of gluconeogenesis. In vitro studies have found that OAA supports glycolysis and mitochondrial respiration fluxes, promotes expression of mitochondrial biogenesis proteins (PGC1α) and enhances SIRT1 phosphorylation [129]. In vivo studies have shown that intraperitoneal injection of OAA in 4-month old C57Bl/6 male mice for two weeks enhances brain bioenergetic pathway protein expression and neurogenesis markers.…”
Section: Mitochondrial Medicine and Alzheimer’s Diseasementioning
confidence: 99%